Toleransi Keagamaan di Klenteng Eng An Kiong, Malang - Bilqis Fahrun Nisa; Diah Ayu Wulan (Jurnal Asosiasi Program Studi Mandarin Indonesia (Jurnal APSMI), 2022)
Tolerance in society is very important. In realizing tolerance, mutual respect and appreciate are needed. Tolerance that is implemented properly will support the birth of a safe, peaceful and harmonious society. However, it is undeniable that in Indonesian society there are many differences, ranging from differences in language, culture, ethnicity and religion or beliefs. This difference can lead to hostility in society if it is not addressed properly. Especially in religious differences, which nowadays often trigger conflicts in society. Within the scope of the temple, it is known the Tridharma, where in one area of worship there are three religions that live in harmony and side by side. This is due to the high level of religious tolerance within the temple. As is the case in the Eng An Kiong temple area, Malang, where Taoists, Confucians and Mahayana Buddhists carry out worship activities in the pagoda. This is an interesting issue to be researched and has significance in realizing an attitude of tolerance in the life of the nation and state. This study aims to describe the behavior of religious tolerance carried out in the Eng An Kiong Temple, Malang. This research was conducted with a descriptive qualitative research method. The data collection method used is a semi-structured interview technique to the temple administrators and religious leaders. The results found are in terms of religious tolerance, there are several things that can be done, namely: worship together, allowing people of different religions to join worship, there is no discrimination and providing halal food during celebrations that are open to the public.